FAMILY AND MARRIAGE IN THE CONTEXT OF THE CONTEMPORARY SOCIAL TRANSFORMATIONS – THE AREA OF THE INTERESTS OF SOCIOLOGY AND SOCIAL WORK - Kawińska, Martyna (Uniwersyteckie Czasopismo Socjologiczne, 2016)
The traditional family model is becoming blurred and for this reason it is no longer valid. Thus, in this changing reality it is worth making an attempt to understand those changes in order to be able to promote appropriately the values which are still most important for the proper functioning of family. The family has always been and will be the central category of social life, around which processes, social phenomena or religious norms are cumulated, but the changing conditions of life of families are generating a necessity to monitor the quality of life of families and look at them as a whole and individually.